2022
DOI: 10.3389/fpsyg.2022.1084961
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of competency and job satisfaction by positive human psychology among physical education teachers at the university level: A systematic review

Abstract: The study aimed to determine how a teacher’s competency at the university level related to professional commitment and job satisfaction. This systematic review intends to determine physical education teachers’ competency and job satisfaction. One of the main objectives of physical education programs is to increase various activities of the student, especially physical activities and participation in it. Students who participate in physical activities feel a variety of emotions, and these may enhance their ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
1
4
0
1
Order By: Relevance
“…Chen and Schaubroeck (2002) concluded that job performance reflects whether a person is effective at what they do or whether they demonstrate good competency. Other studies on the relationship between teacher competency and job performance have confirmed that teacher competency is positively related to job performance (Demir, 2015;Runhaar et al, 2013); that is, the teacher competency level determines individual performance and is a good predictor of individual performance (Yan et al, 2022). Moreover, Rahmatullah (2016) found that increasing teacher competency effectively improved teacher performance among 150 teachers in Indonesia and that continuous learning and competency improvement resulted in higher teacher performance.…”
Section: Competency and Job Performancementioning
confidence: 93%
See 1 more Smart Citation
“…Chen and Schaubroeck (2002) concluded that job performance reflects whether a person is effective at what they do or whether they demonstrate good competency. Other studies on the relationship between teacher competency and job performance have confirmed that teacher competency is positively related to job performance (Demir, 2015;Runhaar et al, 2013); that is, the teacher competency level determines individual performance and is a good predictor of individual performance (Yan et al, 2022). Moreover, Rahmatullah (2016) found that increasing teacher competency effectively improved teacher performance among 150 teachers in Indonesia and that continuous learning and competency improvement resulted in higher teacher performance.…”
Section: Competency and Job Performancementioning
confidence: 93%
“…Human resources refers to the sum of physical and mental resources that people have to contribute to the creation of value and can be utilized by the organization (Armstrong and Taylor, 2009). As universities' most important and core human resources, teachers' overall quality, teaching performance, research performance, and social service ability profoundly impact universities' education level and the quality of talent cultivation (Taylor and Ttyler, 2012;Yan et al, 2022). Competency assessment is the theoretical foundation of and an important tool for HRM (Rajpal, 2016;Katz and Raths, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Another domain that was reviewed is motivation in education, where Yan et al (2022) found that teacher competency at the university level is related to professional commitment and job satisfaction, emphasizing the need for qualified teachers.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Maka, kepuasan kerja pensyarah Kolej Vokasional adalah penting diberi perhatian untuk meningkatkan kualiti pendidikan dan mempromosikan pertumbuhan ekonomi. Antara faktorfaktor yang menyumbang kepada kepuasan kerja seperti keadaan kerja, kedudukan gaji, penyeliaan pengarah, rakan sekerja, dan peluang kenaikan pangkat (Fareza & Tentama, 2020;Setyaningsih & Sunaryo, 2021;Yan et al, 2022).…”
Section: Kajian Literaturunclassified